Diversity of Predatory Arthropods in Soybean (Glycine max L) Refugia - Erise Anggraini; Roy Pardingotan; Siti Herlinda; Chandra Irsan; Muhammad Umar Harun (Politeknik Pertanian Negeri Payakumbuh, 2020)
Many problems arise in the cultivation of crops; one of these problems is insect pests that can threaten crop production. Integrated pest management is an alternative technique for managing the balance of the agricultural environment. Habitat manipulation by increasing plant diversity with refugia is considered an alternative way to maintain natural enemy in an agro ecosystem. The use of soybean as a refugium in a crop field is still limited. Research was conducted to investigate the diversity of predatory arthropods in soybean as a refugium in a chilli pepper crop field at the Agro-technology Training Centre (ATC) at the University of Sriwijaya. In this study, four varieties of soybean (Dena 1, Detam 3 PRIDA, Deja 1, and Devon 1) were used as refugia. Three observation methods were carried out using nets, pitfall traps and visual observation for 7 weeks. The results show that arthropod diversity in soybean plants comprised 6 orders with 10 families and 19 species. Odontoponera denticulata (Hymenoptera) was the most predominant arthropod predator, observed in 73% of all soybean varieties. The number of canopy-dwelling arthropod predators was similar in the four soybean varieties.